2017
DOI: 10.1038/jhh.2016.87
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic differences in prevalence, awareness, control and self-management of hypertension among four minority ethnic groups, Na Xi, Li Shu, Dai and Jing Po, in rural southwest China

Abstract: This study investigates socioeconomic differences in prevalence, awareness, control and self-management of hypertension in rural China. A cross-sectional survey was conducted among four ethnic minority groups in Yunnan Province: Na Xi, Li Shu, Dai and Jing Po. Approximately 5532 consenting individuals aged ⩾35 years (48.4% of whom were male) were selected to participate in the study using a stratified, multistage sampling technique. Information about participants' demographic characteristics and hypertension a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 28 publications
3
16
1
Order By: Relevance
“…This study conducted from 2015 to 2017 provided the updated current status of hypertension in northern China, with a prevalence of 54.5% among women and 57.4% among men. The prevalence of hypertension in the present study was higher than that reported in most other parts of China 13,14,22 and higher than the rates in many other countries 20,[23][24][25][26] . Lu et al also reported a prevalence of 43.3% among women and 46.9% among men in a representative Chinese population aged 35-75 years, during 2014-2017 10 .…”
Section: Discussioncontrasting
confidence: 85%
“…This study conducted from 2015 to 2017 provided the updated current status of hypertension in northern China, with a prevalence of 54.5% among women and 57.4% among men. The prevalence of hypertension in the present study was higher than that reported in most other parts of China 13,14,22 and higher than the rates in many other countries 20,[23][24][25][26] . Lu et al also reported a prevalence of 43.3% among women and 46.9% among men in a representative Chinese population aged 35-75 years, during 2014-2017 10 .…”
Section: Discussioncontrasting
confidence: 85%
“…This study addresses this gap in the literature, with its objective to explore CCSM and any differences a person's gender can make using a flexible Bayesian modelling strategy. It also extends other research that has addressed socioeconomic and/or ethnic discrepancies in CCSM (Cai, Dong, Cui, You, & Golden, ; Van Hecke et al, ) by investigating disparities in gender and related factors when considered jointly.…”
Section: Introductionsupporting
confidence: 61%
“…Some authorities point out that 80% adherence is probably sufficient for most drugs . Chinese hypertensive patients display very poor MA, with reported rates ranging from 40% to 65.8% . Due to the large population base and the rapid increase in better living conditions in China, interventions to improve patients’ MA are more important now than ever.…”
Section: Introductionmentioning
confidence: 99%